O ativismo climático juvenil democratiza a política de soluções baseadas na natureza por meio da tríade da justiça ambiental - Oliveira, Celso Maran de; Amarante Junior, Ozelito Possidonio de; Aragão, Alexandra (Universidade Federal de São Carlos, 2026)
Youth climate activism typically emphasizes global protests, yet institutional models in the Global South remain underexplored. Here we analyze the Young Environmental Ambassadors program in São Carlos, Brazil, where elected high-school students operationalize environmental democracy's three pillars (information, participation, justice) through MPSP facilitated hearings on nature-based solutions (NbS). Questionnaire data (n = 10), interviews (n = 5), and observations (n = 12 meetings) reveal curriculum-aligned training informed council elections and hearings addressing Espraiado Stream water governance, Bicão Park greenspace protection, and Cidade Aracy waste management, yielding Municipal Law 21.458/2023. Prosecutorial facilitation in affected schools positioned youth as community-state mediators, preventing radicalization via institutional channels. This scalable triad integration offers Global South municipalities a replicable NbS governance model, building long-term climate resilience absent in transnational protest frameworks.
Youth climate activism democratizes nbs policy via environmental justice triad
Keywords: Youth climate activism; Nature-based solutions; Environmental justice; Global South governance; Prosecutorial facilitation; CIENCIAS SOCIAIS APLICADAS::DIREITO::DIREITOS ESPECIAIS; 13. Ação contra a Mudança Global do Clima